(untitled) (Letras, 2025)
The following article explores the intersection between bad taste, social stigma, and aesthetic experience in Manuel Mujica Lainez’s 1954 novel La casa. An interpretation from the point of view of these three themes will be given as pillars of the fictional world’s configuration, which indicates a hostile background, closed to the possibility of dialogue, both among the members of the family and between the members’ relationship to the house. This finally results in the family’s extinction and the demolition of the house. The ruminating racconto structure of narration, which aims to reflect upon that which narrates, offers to the reader a tragic world in which the heyday of the family (convergent with the argentine Generation of 80’) falls prey to its own incapacity of decentering and discuss with itself.